2016
DOI: 10.5664/jcsm.5922
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Obstructive Sleep Apnea with Periodic Snoring Sound Recorded at Home

Abstract: According to our results, it is possible to set a periodic snoring threshold (15% or more) for the subject to advance to further sleep studies. Together with medical history and prior to more expensive studies, measuring periodic snoring at home is a simple and useful method for predicting the probability of OSA, in particular among women who are often unaware of their apnea-related snoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…Frequent snoring was detected during feature selection as yet another pertinent feature for OSA prediction, and is part of the minimal feature set for the trained models. Although experts in [63] advise caution in the interpretation of snoring symptoms for assessing sleep apnea, they state it can be reliable when used in conjunction with additional clinical and physical readings, which is the case in our presented work. While the features of insomnia and daytime sleepiness (quantified by ESS) were included in feature selection, they only showed a marginal association with OSA, as opposed to the stipulations of [64,65], respectively.…”
Section: Discussionmentioning
confidence: 80%
“…Frequent snoring was detected during feature selection as yet another pertinent feature for OSA prediction, and is part of the minimal feature set for the trained models. Although experts in [63] advise caution in the interpretation of snoring symptoms for assessing sleep apnea, they state it can be reliable when used in conjunction with additional clinical and physical readings, which is the case in our presented work. While the features of insomnia and daytime sleepiness (quantified by ESS) were included in feature selection, they only showed a marginal association with OSA, as opposed to the stipulations of [64,65], respectively.…”
Section: Discussionmentioning
confidence: 80%
“…[ 17 ] A recent study including 211 participants, aged 18 years and older, showed that there is a strong positive correlation ( r = 0.727, P < 0.001) between periodic snoring sounds measured during home sleep apnea testing and AHI. [ 18 ] Conversely, Hong et al ., while studying the relationship between OSAS severity and snoring time, did not find a linear correlation between the snoring rate and total AHI. However, while comparing the snoring rates between the groups (divided according to the severity of OSAS by AHI), they found that the snoring rates increased as the AHI increased from the control to the moderate OSAS group and decreased as the AHI increased from the moderate to the very severe OSAS group.…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of a recent study consisting of 211 patients undergoing PSG testing, there was strong correlation between periodic snoring and presence of OSAS and the authors have concluded that prior to more expensive studies, measuring periodic snoring at home might be a simple and useful method for predicting the probability of OSA, particularly among women who are often unaware of their apnea-related snoring. 15 Furthermore Akhter et al 16 have shown that it was appropriate to predict mild/ severe OSAS with high sensitivity in REM/non-REM sleep based on snoring/breathing sounds obtained using simple bedside sound receivers.…”
Section: Discussionmentioning
confidence: 99%